Distribution of hemokinin-1 in the rat trigeminal ganglion and trigeminal sensory nuclear complex. (July 2017) - Igawa, Kaori; Funahashi, Hideki; Miyahara, Yu; Naono-Nakayama, Rumi; Matsuo, Hisae; Yamashita, Yoshihiro; Sakoda, Sumio; Nishimori, Toshikazu; Ishida, Yasushi
Highlights: Hemokinin-1 (HK-1) is expressed in small- and medium-sized trigeminal ganglion cells. HK-1 and SP or NeuN coexpress in trigeminal ganglion cells. HK-1 is distributed in the paratrigeminal nucleus and the nucleus caudalis (Vc). HK-1 and SP are localized in lamina I and laminae I and IIo of Vc, respectively. Abstract: Objective: A new mammalian tachykinin peptide encoded in a TAC4 gene was identified and designated as hemokinin-1 (HK-1). A representative of the tachykinin peptide family is substance P (SP), and the function of SP has been well characterized as a pain transmitter or modulator, while it is possible that HK-1 is involved in pruriceptive processing, but, as yet, the distribution of HK-1 peptide in the trigeminal sensory system is still unknown. Thus, the aim of the present study was to elucidate the distribution of HK-1, while comparing the expression of SP, in the trigeminal ganglion and trigeminal sensory nuclear complex. Design: The trigeminal ganglion and the brain stem of male SD rats were used in the immunohistochemical study. Since the amino acid sequence in the carboxyl-terminal regions of HK-1 and SP is common, polyclonal antibodies of HK-1 and SP derived from 6 amino acids consisting of amino-terminal regions of these peptides were produced in guinea pig and rabbit, respectively. The immunohistochemical staining of HK-1 and SP was conducted using frozen sections of the trigeminal ganglion and brain stem in rats. Results: Immunohistochemical studies revealed the expression of HK-1 in small- and medium-sized trigeminal ganglion neurons, in the paratrigeminal nucleus, and in lamina I of the trigeminal nucleus caudalis, while there was no immunoreactivity of HK-1 in the trigeminal nucleus principalis, trigeminal nucleus oralis, and trigeminal nucleus interpolaris. Conclusion: These findings indicate that HK-1 is a target molecule for treatment of itch in the orofaicial regions.